Empowering Women in Gauteng’s Construction Industry: Unveiling Perceived Benefits and Relevance of an Entrepreneurial Development Programme - Elona Ndlovu; Patrick Ebewo (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study investigates the perceived benefits of entrepreneurial coaching for women in a construction accelerator programme in Gauteng, South Africa. Semi-structured interviews were conducted with 15 women entrepreneurs, and thematic analysis was employed to analyse the data. The findings demonstrate that entrepreneurial coaching sessions positively impacted women entrepreneurs and their businesses by enhancing self-efficacy, building relationships, and fostering shifts in vision and entrepreneurial mindset. The programme outcomes for women entrepreneurs included improved technical and innovative building skills, enhanced proficiency in sales, finance, marketing, legal compliance, and overall business growth. The study suggests that programmes supporting women entrepreneurs should prioritise transferring specific skills, such as innovative business modelling, relationship building, visionary capacity development, resilience, and self-efficacy to facilitate business growth. Future research could explore additional areas for entrepreneurial skill development and further investigate the long-term effects of coaching programmes on women entrepreneurs in the construction industry and post-programme support for the participants.